Effects of calcium addition during enzymatic hydrolysis and different pre-treatments on drying duration of brown and white sago sugars - Nurazureen, Matnin (Universiti Malaysia Sarawak (UNIMAS), 2016)
Melroxylon sagu is the starch-producing crop that can produces sago sugar via an enzymatic hydrolysis process. This project has been aiming to identify which pre-treatments (sedimentation and centrifugation) and types of sago sugars can be an alternative to give rise to various qualities of sago sugars. In this project, analyses of white and brown sago sugars were compared by observing the result of drying time, reducing sugar, total phenolic and flavonoid contents, glucose recovery and yield. By the end of this project, sedimentation have been shown to be an excellent pre-treatments of brown sago sugars as it recorded the highest amount of reducing sugar, total phenolic content and total flavonoid content with the shortest drying time (6 days) whereas 221.32 ± 15.54 gIL, 0.099 ± 0.019 mglmL, 0.0097 ± 0.0007 mglmL (without calcium/oven) and 175.44 ± 15.54 giL, 0.091 ± 0.002 mglmL and 0.0119 ± 0.0006 mglmL (with calcium/refrigerator) respectively. Centrifugation is proven to be the most effective pre-treatments as it recorded the highest production of brown sago sugars, which is 298.5 ± 30.41 g (without calcium) and 346.5 ± 6.36 g (with calcium) and yield the finest, powder-like and lighter color of brown sago sugars (with and without calcium). Besides, white sago sugar (without calcium) have the best reducing sugars (175.15 ± 11.l2), TPC (0.00049 ± 0.00046) and TFC (0.00014 ± 0.00012). It is also revealed that white sago sugars (without calcium) have the best results for drying time (6 days), production of white sago sugars (283 ± 10.82 g), glucose recovery (97.30 ± 6.18 %), glucose yield (80.99 ± 5.82 %) and yield the finest, powder-like and whiter color of white sago sugars. However, it does not give different results despite adding calcium in white sago sugars as ANOV A indicated that p = 0.674 (final mass), p = 0.956 (glucose recovery) and p = 0.780 (glucose yield) at (l = 0.05.